Positive End-Expiratory Pressure Setting in COVID-19-Related Acute Respiratory Distress Syndrome: Comparison Between Electrical Impedance Tomography, PEEP/FiO2 Tables, and Transpulmonary Pressure - Gibot, Sébastien; Conrad, Marie; Courte, Guilhem; Cravoisy, Aurélie (Frontiers in Medicine, 2021)
Introduction: The best way to titrate positive end-expiratory pressure (PEEP) in patients suffering from acute respiratory distress syndrome is still matter of debate. Electrical impedance tomography (EIT) in a non-invasive technique that could guide PEEP setting based on an optimized ventilation homogeneity. Methods: COVID-19 related ARDS patients admitted to the ICU in March 2021 requiring mechanical ventilation were enrolled. Patients were monitored by an esophageal catheter and a 32-electrode EIT device. Within 48 hours after the start of mechanical ventilation, different levels of PEEP were applied based upon PEEP/FiO2 tables, positive end-expiratory transpulmonary (PL)/ FiO2 table, and EIT. Respiratory mechanics variables were recorded. Results: Seventeen patients were enrolled. PEEP values derived from EIT (PEEPEIT) were different from those based upon other techniques,with poor in-between agreement. PEEPEIT was associated with lower plateau pressure, mechanical power, transpulmonary pressures, and with a higher static compliance (Crs) and homogeneity of ventilation. Conclusion: Personalized PEEP setting derived from EIT may help to achieve a more homogenous distribution of ventilation. Wether this approach may translate in outcome improvement remains to be investigated.